Grendel Grendel Grendel Animating Beowulf - Torre, Dan (Animation: Key Films/Filmmakers, 2021)
This open access study of the film Grendel Grendel Grendel, directed by Alexander Stitt, presents it as a masterpiece of animation and design which has attained a national and international cult status since its release in 1981. The film, based on the novel, Grendel, by John Gardner, is a loose adaptation of the Beowulf legend, but told from the point of view of the monster, Grendel. Grendel Grendel Grendel is a mature, intelligent, irreverent and quite unique animated film - it is a movie, both in terms of content and of an aesthetic that was well ahead of its time. Along with a brief overview of Australian animation and a contextualization of where this animated feature fits within the broader continuum of Australian (and global) film history, Dan Torre and Lienors Torre provide an intriguing analysis of this significant Australian animated feature. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com.